Clinical Evaluation of Portable Wound Volumetric Measurement Devices. (August 2018) - Chiang, Nathaniel; Rodda, Odette A; Kang, Anna; Sleigh, Jamie; Vasudevan, Thodur
ABSTRACT: OBJECTIVE: Wound dimensional assessments are important in determining the progress of a wound and the effect of interventions on wound healing. The FastSCAN (FS; Polhemus Inc, Colchester, Vermont) and Silhouette Mobile (SM; ARANZ Medical, Christchurch, New Zealand) are portable devices that quantify surface area, depth, and volume of wounds. This study evaluated their reliability in producing accurate wound measurements. DESIGN AND SETTING: This study was conducted at the Waikato Hospital, Hamilton, New Zealand. PATIENTS AND INTERVENTION: Eleven vascular patients with a combined total of 16 wounds underwent simultaneous wound measurements using three-dimensional computed tomography (CT) reconstruction, FS, and SM. MAIN OUTCOME MEASURE: The validity of FS and SM was tested against CT. Additionally, the interoperator reliability and intraoperator reliability of FS and SM were determined. MAIN RESULTS: The intraoperator reliability and interoperator reliability for volume recordings of the SM were 0.97 and 0.97, respectively, and for the FS were 0.96 and 0.97, respectively. The FS and SM measurements were not significantly different from CT. The SM consistently produced smaller wound volume and depth measurements compared with CT. In contrast, overestimation was observed for FS when compared with CT. However, the volume measurements in one wound were anomalous, being 10 times larger than CT measurements. Excluding this wound, there were strong correlations in wound volumes for SM and CT ( r = 0.81; P ⩽ .0001), for FS and CT ( r = 0.99; P ⩽ .001), and for SM and FS ( r = 0.99; P ⩽ .0001). CONCLUSIONS: Measurements from FS and SM were comparable to CT. Therefore, SM and FS devices both offer the benefit of being noncontact portable devices that produce reproducible and reliable readings.